The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12883-020-01781-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of combined cerebrospinal fluid physicochemical parameters to detect intracranial infection in neurosurgery patients

Abstract: Routine test of cerebrospinal fluid (CSF), such as glucose concentrations, chloride ion, protein and leukocyte, as well as color, turbidity and clot, were important indicators for intracranial infection. However, there were no models to predict the intracranial infection with these parameters. We collected data of 221 cases with CSF positive-culture and 50 cases with CSF negative culture from January 1, 2016 to December 31, 2018 in the First Affiliated Hospital of Nanchang University, China. SPSS17.0 software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It’s been reported that postoperative infection in patients with cerebrovascular diseases, craniocerebral trauma and craniocerebral tumors is relatively high, and its possible causes are closely related to the types of surgery, surgical methods and the characteristics of surgery in patients with this disease [ 15 , 16 ]. Patients with cerebrovascular diseases and craniocerebral injuries mainly undergo emergency surgery in clinical settings, and there are often insufficient pre-operative preparations and incomplete debridement during surgery [ 17 ]. Therefore, patients have a relatively high risk of intracranial infection.…”
Section: Discussionmentioning
confidence: 99%
“…It’s been reported that postoperative infection in patients with cerebrovascular diseases, craniocerebral trauma and craniocerebral tumors is relatively high, and its possible causes are closely related to the types of surgery, surgical methods and the characteristics of surgery in patients with this disease [ 15 , 16 ]. Patients with cerebrovascular diseases and craniocerebral injuries mainly undergo emergency surgery in clinical settings, and there are often insufficient pre-operative preparations and incomplete debridement during surgery [ 17 ]. Therefore, patients have a relatively high risk of intracranial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing CSF aids the diagnosis of CNS diseases . The routine clinical analysis of CSF relies on cell culture, latex agglutination tests, and immunologic and biochemical analyses. , Despite being well established, these methods have intrinsic limitations, such as complicated sample pretreatment, large sample consumption, long response time, etc. In our method, 1 μL of CSF was directly spotted on the self-assembled AuNP arrays for LDI-MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the reduction of CSF glucose levels is a clinical sign of bacterial CNS infection. , For absolute quantification of glucose in CSF, cellobiose was introduced as an internal standard (IS) due to its similar ionization efficiency compared to glucose. As shown in Figure f, peaks at m / z 203 and 365, corresponding to [glucose + Na] + and [cellobiose + Na] + , could be clearly detected by the ISANAS-assisted LDI-MS from 1 μL of artificial CSF containing different concentrations of glucose and 1 mM cellobiose.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated protein levels and red blood cell counts in CSF were also detected in patients with viral encephalitis (14)(15)(16). Studies have shown that lower chloride levels (<120 mEq/L) might be seen in tuberculous, cryptococcal and bacterial meningitis (17,18).…”
Section: Discussionmentioning
confidence: 99%